The anti-apoptotic effect of fluid mechanics preconditioning by cells membrane and mitochondria in rats brain microvascular endothelial cells. (1st January 2018) - Tian, Shan; Zhu, Fengping; Hu, Ruiping; Tian, Song; Chen, Xingxing; Lou, Dan; Cao, Bing; Chen, Qiulei; Li, Bai; Li, Fang; Bai, Yulong; Wu, Yi; et al.
Highlights: The intervention of fluid mechanics preconditioning could inhibit the apoptosis of rat brain microvascular endothelial cells. Laminar shear stress of fluid mechanics activated Tie-2 on the cells membrane surface and Bcl-2 on the mitochondria for anti-apoptosis. Fluid mechanics preconditioning proved to be the mechanical brain protection effect. Abstract: Exercise preconditioning is a simple and effective way to prevent ischemia. This paper further provided the mechanism in hemodynamic aspects at the cellular level. To study the anti-apoptotic effects of fluid mechanics preconditioning, Cultured rats brain microvascular endothelial cells were given fluid intervention in a parallel plate flow chamber before oxygen glucose deprivation. It showed that fluid mechanics preconditioning could inhibit the apoptosis of endothelial cells, and this process might be mediated by the shear stress activation of Tie-2 on cells membrane surface and Bcl-2 on the mitochondria surface.